MANAJEMEN PENDIDIK BERBASIS KEARIFAN LOKAL - Fu`ad Arif Noor (UPI Kampus Cibiru, 2020)
This study is to explain the management of educators based on Indonesian local wisdom or culture, especially in Yogyakarta, which teaches students to be attached to real situations and conditions they face. The pillars of local wisdom educators in the form of: 1) growing educated people based on the recognition of the existence of personality since in the womb, 2) education based on the truth and virtue (Akhlak Mahmudah), avoiding ways of thinking that are not true and gratuous (in a hurry) gesa) or sulaton waton (origin problematic), 3) education that delivers moral, spiritual (affective domain) domains, as well as being able to internalize body and soul, not merely cognitive or psychomotor domains, and 4) synergize with culture, education and tourism which are very need to be developed in synergy in character education.